2002
DOI: 10.1080/07399330290107502
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Families of Female-Headed Households in Botswana: A Secondary Analysis of Case Studies

Abstract: Previous studies note a positive relationship between female-headed households (FHHs) and poverty in urban and rural areas of Botswana. To explore this further, data were collected from 7 FHHs through participant observation and open-ended interviews. A secondary analysis of data described the quality of life (QOL) of members of the households according to one's ability to meet basic human needs (food, water, shelter, safety, and health). FHHs ranged in age from 40-91 years, with family size ranging from 1-11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…However, bearing in mind the controversy related to measurement of poverty (see Aaberge and Mogstad 2007), the 25% level of (extreme) poverty is considered tentative. In view of the feminization of poverty theory, our observation that female-headed households were more likely to be transitorily poorer than their male counterparts is consistent with other findings (see Akinsola and Popovich 2002). However, we find no evidence of gender difference in the experience of extreme poverty, and this requires some comment.…”
Section: Discussion and Policy Implicationssupporting
confidence: 81%
“…However, bearing in mind the controversy related to measurement of poverty (see Aaberge and Mogstad 2007), the 25% level of (extreme) poverty is considered tentative. In view of the feminization of poverty theory, our observation that female-headed households were more likely to be transitorily poorer than their male counterparts is consistent with other findings (see Akinsola and Popovich 2002). However, we find no evidence of gender difference in the experience of extreme poverty, and this requires some comment.…”
Section: Discussion and Policy Implicationssupporting
confidence: 81%
“…However, bearing in mind the controversy related to measurement of poverty (Aaberge & Mogstad, 2007), the poverty levels deserve further consideration. In view of the feminization of poverty theory, our observation that female headed households were more likely to be transitorily poorer than their male counterparts is consistent with other findings (Akinsola & Popovich, 2002). However, we find no evidence of gender difference in the experience of extreme poverty and this requires some comment.…”
Section: Discussion and Policy Implicationssupporting
confidence: 82%
“…However, two of the issues that concern the government and public a great deal are unemployment (especially among young professionals) and poverty. It was generally acknowledged that rural households were generally poor with the majority being female-headed households (Akinsola & Popovich, 2002). The Botswana Institute for Development Policy Analysis estimated that in 1993/94, 47% of Botswana citizens lived below the poverty line and it was argued that this figure reflected substantial decline in poverty since 1985/86 (BIDPA, 1997.…”
Section: Botswana Profilementioning
confidence: 99%
“…This suggests that male and female learners experience learning autonomy differently. In the context of Botswana research has shown that 47% of households are female headed (Akinsola & Popovich, 2002)., These results are therefore not surprising because even though these women have enrolled for full-time studies, they still have family commitments which they often have to balance with university course commitments. This finding is in line with women elsewhere as revealed by Johnson, Schwartz, and Bower (2010) which shows that many women who enrolled to further their education were not able to complete their programmes since they could not cope with double or triple burdens of family, job, and school.…”
Section: Findings and Discussionmentioning
confidence: 89%